(untitled) (Journal of Economic Research & Business Administration, 2016)
As it might be commonly known, innovation is not only around novelty, but also might be considered along with the necessity of its practical implementation and market realization. This in turn, provides a positive impact (economic, scientific, technological, social) on both market and society. Such a case, with no doubt, appears quite an illustration of what opportunities innovation allows the company to open on one hand, and causesto innovation risks increase on an other one. This in turn, for such risks tracking, analysis and further management the reliablemethods are strictly required.